PREDICTIONS OF LiFePO4 BATTERY DISCHARGING TEMPERATURE USING AUTOREGRESSIVE INTEGRATED MOVING AVERAGE AND HOLT'S DOUBLE EXPONENTIAL SMOOTHING - Revano Mege, Christio
Alternative energies become the solution in the middle of global climate change due to CO2 emissions. However, alternative energies such as wind power and solar cell are intermittent that require energy storage such as batteries. Lithium ion batteries are in the frontline as energy storage for electricity produced by alternative energy. One of the benefits from this kind of energy storage is the high energy density. However, performances of lithium cells in a module highly depend on operating temperature between 00C – 400C. Temperature increasing that exceeds the limit can significantly reduce battery performances Therefore, temperature predictions are required in order to know when battery could exceed the 400C limit.